Analysis of microstrip antennas with chiral metamaterials substrates by method of singular integral equations - A.M. Neshcheret (Физика волновых процессов и радиотехнические системы, 2018)
This article is devoted to the development of correct methods of electrodynamic analysis of microstrip antennas with substrates of chiral metamaterials. The method of analysis of such antennas based on the method of singular integral representations of the field and the method of surface impedances is proposed. A singular integral equation for the unknown function of the current density distribution over the radiator is obtained. Two methods of solving this equation are shown: the method of moments and the method of partial reversal of the operator. A convergence study was conducted. The approbation of the proposed method on the example of solving the test problem using the Feko software complex is performed.